2017
DOI: 10.5194/hess-2017-415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaporation suppression and energy balance of water reservoirs covered with self-assembling floating elements

Abstract: Abstract. The growing pressure on natural fresh water resources and projected climate variability would expand the need for water storage during rainy periods. Evaporative losses present a challenge to efficient water storage reservoirs, especially in arid regions with chronic water shortages. Among the various methods for suppressing evaporative losses, the use of self-assembling floating elements offers 10 a simple and scalable solution especially for small reservoirs. The use of floating elements is not new… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The water and cover surface temperatures were computed from 1D considerations ignoring thermal feedbacks between water and air temperatures that could affect surface water temperature in the gaps between the covers. In Aminzadeh et al (), the temperatures of the surface water in the gaps and evaporation rates were obtained simultaneously by accounting for lateral heat exchanges between cover and water (still within an essentially 1D‐surface energy balance formulation). In this study, we apply a simpler approach by considering coupling between surface energy balance of water and floating cover elements.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The water and cover surface temperatures were computed from 1D considerations ignoring thermal feedbacks between water and air temperatures that could affect surface water temperature in the gaps between the covers. In Aminzadeh et al (), the temperatures of the surface water in the gaps and evaporation rates were obtained simultaneously by accounting for lateral heat exchanges between cover and water (still within an essentially 1D‐surface energy balance formulation). In this study, we apply a simpler approach by considering coupling between surface energy balance of water and floating cover elements.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Assouline et al (, ) provided several insights into estimating evaporation suppression, demonstrating that evaporation losses are typically higher than the uncovered area fraction, especially as the gaps in the cover become smaller (for the same total uncovered area). In a recent numerical study of evaporation from water reservoirs, Aminzadeh et al () demonstrated that for gaps between floating elements of centimeter size, the expected evaporation suppression with maximal floating covers was about 80%, supporting the potential of self‐assembling floating elements as an effective evaporation suppression method. Interestingly, estimated evaporation suppression was similar for black and white covers despite the effect of color on radiation and energy partitioning.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…This reduction is very relevant if we are in arid zones or for example for waste water basins where an adequate water coverage can save from 10,000 to 20,000 m 3 per ha. Several calculations have been done using Penman model [19] and experimental findings of several authors (see for example [27] and [28]) support this rough estimate. However, in the case of HPP, saving water is not the main concern so this is mentioned for completeness but not a major factor compared to the potential increase in energy production from FPV.…”
Section: Main Textmentioning
confidence: 74%